Therapy of Skin Diseases A Worldwide Perspective on Therapeutic Approaches and Their Molecular Basis - Krieg, Thomas; Bickers, David R.; Miyachi, Yoshiki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Impressive progress has been made in understanding the molecular basis of skin diseases. This has led to the development of novel therapeutic approaches. This truly international and lavishly illustrated textbook is written for dermatologists in Europe, America and Asia. This book: Provides the reader with up-to-date information on skin disease therapy Helps the reader understand the mode of action of new and established therapies Furthers the understanding of ongoing and new developments in the field Is written and edited by international and renowned dermatology experts from Europe, America, and Asia Includes regional therapy concepts Has a user-friendly structure including key points and practical hints for indications and applications in each chapter By explaining the molecular background of skin diseases, this book helps the reader choose the most appropriate novel or classical therapy for the patient and thus reach a better treatment outcome. It will be an indispensable resource for dermatologists in university departments as well as in clinical practice.
Biology of the Skin -- Immune Mechanisms -- General Pharmacology -- Immunomodulation in Dermatology -- Basic Principles of Genetics and Gene Therapy -- Percutaneous Absorption and Principles of Corneotherapy/Skin Care -- Principles of Systemic Therapy -- Retinoid Pharmacology -- Ultraviolet (UV) A and (UV) B Phototherapy -- Laser Therapy -- Photodynamic Therapy -- Dermatologic Surgery -- Neurophysiology of Itch -- Infectious Diseases -- Bacterial and Mycobacterial Infections -- Fungal Infection -- Viral Infections -- Sexually Transmitted Diseases (STDs) -- Human Immunodeficiency Virus (HIV) -- Ectoparasitic and Protozoan Diseases -- Papulosquamous Dermatoses -- Psoriasis -- Parapsoriasis and Related Disorders -- Lichen Planus -- Atopic Dermatitis and Related Diseases -- Atopic Dermatitis -- Pruritus -- Urticaria -- Mastocytosis -- Allergic Reactions and Hypersensitive Diseases -- Allergic Contact Dermatitis -- Photosensitivity Diseases -- Drug Reactions -- Hypersensitivity Syndrome Reaction -- Eosinophilic Dermatoses -- Neutrophilic Dermatoses -- Skin Manifestations in Rheumatologic Disorders -- Acne and Rosacea -- Acne and Its Variants -- Rosacea and Related Diseases -- Autoimmune Diseases -- Acquired Bullous Disease -- Connective Tissue Diseases -- Cutaneous Vasculitis -- Graft-Versus-Host Disease -- Vitiligo -- Therapy of Noninfectious Granulomatous Diseases -- Metabolic Diseases -- The Porphyrias -- Deposition Diseases -- Cosmetic Dermatology -- Hair Diseases (Alopecia Areata and Androgenetic Alopecia) -- Nail Diseases -- Hyperhidrosis -- Disorders of Pigmentation -- Cosmetic Surgery -- Inherited Diseases -- Inherited Bullous Diseases -- Inherited Keratinocyte Diseases (Ichthyosis and Related Disorders) -- Immunodeficiency Disorders -- Disorders of DNA repair -- Benign and Malignant Tumors -- Nonmelanoma Skin Cancer -- Malignant Melanoma -- Treatment of Cutaneous Lymphomas -- Vascular Malformations -- Rare Malignancies of the Skin -- Miscellaneous Disorders -- Diseases of Pregnancy and Their Management -- Pediatric Dermatology -- Aging and Photoaging of the Skin -- Occupational Dermatoses -- Wound Healing.
Keywords: Medicine; Dermatology; Family medicine; Oncology; Medicine & Public Health; Dermatology; General Practice / Family Medicine; Oncology